THE MULTI-FUNCTIONAL APPLICATION OF TEACHERS - Husni Husni; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2019)
This study aims to obtain a picture of the multi-functional application of teachers. In addition, it is also to find out its effect on learning achievement in school. This study uses data collection methods, namely observation, documentation, interviews, and questionnaires. The object of the study population is the Modern Islamic boarding school is a teacher by taking or setting ten teachers. The results showed that (1) the level of application of multi-function teachers in Modern boarding schools is in the medium category, the multi-function effectiveness of teachers in achieving student learning achievement can be done with examine the supporting and inhibiting factors, so that solutions can be sought.